SOME COMMENTS ON THE RELATIONSHIP BETWEEN RESTRICTION OF FREEDOM AND CONDITIONAL SENTENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The similarities and differences between restriction of freedom and conditional sentence according to the Criminal Law of the Republic of Uzbekistan are analyzed in this article. The researcher tried to justify that they are separate institutions.